Oral health program aimed at prevention in early childhood - Sandra Fettolini; Ismael Morales Ojeda; Marcos Parada; Miguel Meriño Morales (Medisur)
Background: oral health care in infants is essential, since at this age habits of adequate nutrition and hygiene are established, which allow a correct cultural and psychosocial development. Objective: to evaluate a dental program aimed at oral health care in infants. Methods: quasi-experimental study, with educational intervention, applied to 100 infants, in Nogoyá, who participated together with their tutors in three educational workshops. An evaluation was carried out at the beginning and end of these. To compare the before and after population, the Mann Whitney U test was used, with a significance level of 95%. Results: when analyzing the initial and final evaluation, it was established that the program significantly improved the results regarding the O'leary index of plaque distribution (p<0.001), gingival index (p<0.001), and oral hygiene (p< 0.001). After conducting educational workshops, the consumption of cariogenic foods was reduced. Conclusions: the program carried out allowed reducing the levels of plaque, gingivitis, improving hygiene and healthy eating in infants.